The making of rights of nature: nine patterns in a decade of empirical research on social-ecological drivers and actors - Ilkhom Soliev; Frauke Pirscher; Marie Schreiber (Environmental Research Communications)
Rights of Nature (RoN) cases, where nature is granted legal rights, are rapidly gaining traction across the globe. Although there are many individual and comparative case studies, the extent to which emerging RoN cases share specific patterns that can be observed in the processes leading to the adoption of RoN is yet to be understood. To fill this gap, we provide a systematic literature review of the decade of empirical research on the RoN. Building on the Institutional Analysis and Development framework, our review uses an in-depth analysis, with a special focus on eliciting evolving patterns across cases. The analysis demonstrated that the drivers of RoN processes are extraordinarily complex and case-specific, shaping our understanding of RoN itself. The identified nine patterns show that understanding RoN as a ‘revolutionary ecocentric movement’ is too simplistic, and it should rather be understood as a boundary object that connects place-based non-human and human well-being and relations, as well as formal and informal institutional conditions. The review revealed that themes such as justice, property rights, and personal engagement of powerful actors have been key in driving RoN cases worldwide. Likewise, contrary to the conventional perception, concern for the environment is not a common driver of RoN, and Indigenous or local communities cannot be universally and simply described as advocating actors for RoN, while undoubtedly it is often their interests that are most affected by RoN reforms. However, RoN-related rules tend to create space for questioning the purely instrumental and short-term perspectives towards nature and for redirecting the focus to relational and representational thinking. We found that disciplinary silos contributed to the historically veiled image of RoN due to insufficient engagement with interdisciplinary and decolonizing research methods. The revealed patterns can guide scholars, practitioners, and policymakers in rapidly growing cases worldwide to learn from the existing empirical knowledge. Our study is particularly valuable in times when multiple local-to-global and increasingly acute challenges around nature and biodiversity are putting pressure on societies to develop more ‘fundamental’ or ‘transformative’ approaches bridging science, policy, and practice and especially those that can better integrate diverse knowledge systems of Indigenous and local communities.